KEDUDUKAN ANAK DALAM AKTIFIITAS POLITIK BERDASARKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Hendri, Melani; Artina, Dessy; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The involvement of children in political campaigns is a violation of children's rights in accordance with law number 35 of 2014 concerning child protection. However, in the concept of a democratic state, everyone has the right to participate in government. The non-uniformity of laws and regulations regarding the age limit of children results in clashing with one another. This of course creates legal uncertainty for children and confusion in the community regarding which rules must be obeyed.The type of research used in this legal research is the normative juridical method, with a study of legal principles, namely the principle of legal certainty. Research is descriptive in nature, which is a study that aims to make a clear and detailed description of the problem. The data source used is secondary data. The data collection technique used in this study was the literature review method after the data was collected and then analyzed to draw conclusions.From the results of research and discussion it is known that, firstly, there is no uniformity of laws and regulations regarding child age limits, so a uniformity of laws and regulations is needed, secondly, harmonization is expected to pay attention to principles, content material and hierarchy so that a legal rule reflects harmony and suitability. with other national laws and regulations, third, the government needs to make legal reforms by revising laws and regulations as an effort to uniform the age limit of children in Indonesia.Keywords: Child- Political Activity – Laws And Regulations